GRDB 14 FL: rice variety available for seeds production and commercialization in Guyana - CGIAR Research Program on Rice (2019)
GRDB 14 is available for seeds production and commercialization in Guyana. The GRDB selected this variety based on its agronomic performance and grain quality. In 2016 about 16% of the available seeds for rice sowing corresponds to this variety